(untitled) (Tokyo, 1973)
The plan of the contest was to go beyond interpretations and evaluations of Japan already astablished by leading authorites and to attempt to evolve a new image of Japan in the rapidly altering conditions of today.
Keywords: National characteristics, Japanese